Cash Flow Risk and Financial Balance: Evidence from Islamic Rural Banks in Indonesia - Hendri, Zul; Shuib, Sollehudin; Widarjono, Agus; Sintarini, Fitriasari (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This study delves into the impact of funding liquidity risk (FLR) counting, including several bank-specific variables and the Coronavirus outbreak, on the balance of Islamic rural banks (IRBs) in Indonesia. Utilizing unbalanced quarterly panel data from 97 IRBs in Java from 2015 (Q1) to 2023 (Q4), the analysis is conducted using panel data regression. The results confirm that FLR significantly decreases bank stability. However, this negative influence was notably weakened during the COVID-19 Crisis. The analysis further reveals that the negative outcome of FLR on stability is more pronounced in smaller IRBs compared to their larger counterparts. Additionally, the findings show that while bank capital and operational efficiency enhance balance, factors such as larger bank size, high financing levels, and the pandemic period itself tend to reduce it. This research offers two key implications. Theoretically, it highlights how FLR can erode stability, a risk amplified when banks undertake high-risk investments. Practically, it underscores the critical need for especially the smaller IRBs to proactively manage asset-liability maturity mismatches to ensure financial stability.